The Influence Of Work Ability, Work Motivation, Work Situation, Job Satisfaction And Compensation System On Work Achievement Of Employees In The District Of Transportation Of Muara Enim - Reza Pahlevi; Abdul Hamid; Darmin Darmin (Penerbit Jurnal Indonesia, 2023)
Research with the aim to determine and analyze the effect of work ability, work motivation, work situation, job satisfaction and compensation system partially and simultaneously on the work performance of employees of the Muara Enim District Transportation Office. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. The results of the study showed that work ability has a significant effect on the work performance of employees of the Muara Enim District Transportation Office. Work motivation has a significant effect on work performance. Work situation has a significant effect on work performance. Job satisfaction has a significant effect on work performance. The compensation system has a significant effect on work performance. Work ability, work motivation, work situation, job satisfaction and the compensation system have a jointly significant effect on the work performance of employees of the Muara Enim District Transportation Office.